Parental Occupational Exposures and Risk of Childhood Acute Leukemia - Kyriakopoulou, Aleka (Mater Sociomed, 2018)
INTRODUCTION: Acute leukemia, accounting for 20% of all cancers diagnosed in individuals younger than 19 years old, is the most prevalent childhood malignancy. Among environmental risk factors, parental occupational exposures have attracted scientific interest as potential predisposing factors for childhood leukemia. The role of parental occupational exposure to social contacts, harmful chemicals, electromagnetic fields and ionizing radiation has been investigated with conflicting and inconsistent results. AIM: A case-control study aiming to assess the association between parental occupational exposures to social contacts, chemicals and electromagnetic fields and the risk of offspring acute leukemia. MATERIAL AND METHODS: 108 children with acute leukemia and equal number of matched controls were included. Data on parental occupations before conception, during pregnancy, during breastfeeding and after birth, and on potential risk factors was recorded. Associations between parental exposure and risk of childhood leukemia were estimated. RESULTS: Parental occupational exposure during the four periods of exposure was not associated with childhood leukemia. High birth weight and family history of cancer were associated with the development of childhood acute leukemia. A weak association of maternal medication use during pregnancy and leukemia risk emerged. CONCLUSIONS: Since the causative factors of childhood leukemia remain unknown, further investigation is mandatory for the reduction of disease burden.